2014
DOI: 10.1027/0269-8803/a000119
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Locked and Response-Locked ERP Correlates of Spatial Inhibition of Return (IOR) in Old Age

Abstract: Behavioral research has shown that Inhibition of Return (IOR) is preserved in old age although at longer time intervals between cue and target, which has been interpreted as reflecting a later disengagement from the cue. A recent event-related potential (ERP) study attributed this age-related pattern to an enhanced processing of the cue. Previous ERP research in young samples indicates that target and response processing are also affected by IOR, which makes interesting to study the ERP correlates of IOR from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 90 publications
(224 reference statements)
1
14
0
Order By: Relevance
“…Previous ERP results in our laboratory with the same task employed in the present experiment have shown IOR-related reductions in the amplitude of R-LRP also in the LVF that have been related to reduced/inhibited response preparation to spatially cued targets (see Amenedo et al, 2014). Taking into account the above studies in the context of somatosensory spatial attention and mu modulations, and our previous response-locked ERP results, the synchronization of preresponse mu rhythm observed in the present study under spatial IOR could be related to an attention-driven reduction of somatomotor processing that leads to power increases prior to the execution of responses to target stimuli that are presented at previously cued locations and whose visual processing has been reduced (see also Gutiérrez-Domínguez et al, 2014).…”
Section: Lvf Mu (9-11 Hz) and Beta (28-32 Hz) Bandssupporting
confidence: 63%
See 4 more Smart Citations
“…Previous ERP results in our laboratory with the same task employed in the present experiment have shown IOR-related reductions in the amplitude of R-LRP also in the LVF that have been related to reduced/inhibited response preparation to spatially cued targets (see Amenedo et al, 2014). Taking into account the above studies in the context of somatosensory spatial attention and mu modulations, and our previous response-locked ERP results, the synchronization of preresponse mu rhythm observed in the present study under spatial IOR could be related to an attention-driven reduction of somatomotor processing that leads to power increases prior to the execution of responses to target stimuli that are presented at previously cued locations and whose visual processing has been reduced (see also Gutiérrez-Domínguez et al, 2014).…”
Section: Lvf Mu (9-11 Hz) and Beta (28-32 Hz) Bandssupporting
confidence: 63%
“…In the research context of the present results, the visual field has been found to be an important factor affecting IOR effects on visual and response-related ERP activity with the same task design (Amenedo et al, 2014;Gutiérrez-Domínguez et al, 2014). In those studies, when comparing location-cued trials with the uncued trials, the target-locked ERPs showed significant spatial IOR effects that differed between visual fields in several components.…”
Section: Uvf Beta Band (26-28 Hz)mentioning
confidence: 50%
See 3 more Smart Citations